Il femminile nella coscienza. Un’analisi attraverso il simbolismo teologico - Castellano, Marilisa (Alpha omega, 2021)
The theme of the present work does not intend to be a specifically linguistic study of gender difference, but rather a study of the analogical character of the symbolism of the man-woman couple, starting from that specific place which is that of the biblical text. The theme of conscience was present even in the study of monks, something which represents the central event of Christian interiority: the specific function of moral discernment. Starting from medieval monasticism, this study will trace how conscience has been designated with feminine features.